Berlin heute : = Berlin today = Berlin aujourd'hui - Kruse, Christiane; Haddenhorst, Michael; Hohmuth, Jürgen (Prestel, 2002)
"Berlin heute" hat viele Gesichter und wird dabei als Ganzes wieder zu einer europäischen Metropole mit faszinierender Ausstrahlung. Kaum eine Stadt der Welt befindet sich in einem so tiefgreifenden Verwandlungsprozess wie Berlin. Nach den Zerstörungen des Zweiten Weltkriegs und Jahrzehnten der Trennung in Ost und West, findet das wiedervereinigte und in der Folge auch wieder zur Hauptstadt erklärte Berlin zu einer neuen architektonischen Gestalt. - Focusing on 35 distinct areas of the city, this book presents the new face of the German capital, including the former West, the new centre and the government district, in photographs that look at the contrasts between new and old. Architectural historian Christiane Kruse examines Berlin's past, offering insights into its rebirth as a thriving, thoroughly modern metropolis and using texts that place current developments in a historical context. Rare, archive photographs from the GDR and before the war show the remarkable transformation of the city.